2013
DOI: 10.4317/jced.51042
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of recurrent aphthous ulceration experience in patients attending Piramird dental speciality in Sulaimani City.

Abstract: Objective: The aim of this study is to report the prevalence and risk factors of recurrent aphthous ulceration (RAU) in patients attending Piramird dental speciality for seeking dental treatment. Study design: A cross-sectional survey was carried out among patients (n=1100) who were visiting the department of oral medicine at Piramird dental speciality center in Sulaimani from December 2011-February 2012. The age range of the patients were between 10-79 years, with mean age of (34.27±14.14). 446 (44.6%) of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
34
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 29 publications
11
34
0
7
Order By: Relevance
“…These findings are comparable to studies of Mehrotra et al 16 In present study Apthous ulcers were most commonly found in 21-30 years of age group (29.2%) with mean age of 36.5 years which is comparable with study of M. Abudullah. 17 In present study male to female ratio was (M:F : 1.8:1) which is comparable with the study of Mathew et al (M:F : 2.1:1). 18 Gender wise distribution is comparable with Mathew et al 18 But this is in contrast with study of M. Abdullah where (M:F : 0.6:1).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings are comparable to studies of Mehrotra et al 16 In present study Apthous ulcers were most commonly found in 21-30 years of age group (29.2%) with mean age of 36.5 years which is comparable with study of M. Abudullah. 17 In present study male to female ratio was (M:F : 1.8:1) which is comparable with the study of Mathew et al (M:F : 2.1:1). 18 Gender wise distribution is comparable with Mathew et al 18 But this is in contrast with study of M. Abdullah where (M:F : 0.6:1).…”
Section: Discussionsupporting
confidence: 82%
“…18 Gender wise distribution is comparable with Mathew et al 18 But this is in contrast with study of M. Abdullah where (M:F : 0.6:1). 17 Most common site for the Apthous ulcer in present study was found to be tongue (47.9%), but Abdullah in their study found Lip and buccal mucosa as the most common site (71.1%). 17 In present study Leukoplakia was most commonly found in 20-40 years age group with male preponderance and most common site of involvement was buccal mucosa.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Recurrent aphthous stomatitis has been reported to be more common among women, among persons in the second and third decade of life, and among students (Abdullah, ; Axéll & Henricsson, ). Men had lower odds of having RAS than women in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that such studies give a prevalence much greater than those adhering to the RAS definition. Reported estimates vary between 1.5 and 28 % in different parts of the world, suggesting that there may be genetic differences to account for these geographical variances [2][3][4]. The prevalence in children may be greater than adults [5,6] Aetiology An impressive array of factors has been implicated in the aetiology of RAS, although it is likely that many of them influence the nature of the disease rather than cause it.…”
Section: Introduction Diagnosismentioning
confidence: 95%